Pretreatment of red palm oil extracted from palm fruit (Elaeis guineensis) attenuates carbon tetrachloride induced toxicity in Wistar rats - Okezie Emmanuel; Ugochukwu M. Okezie; Emeka J. Iweala; Eziuche A. Ugbogu (Elsevier, 2021)
Background: Red palm oil (RPO) is antioxidant rich oil extracted from palm tree (Elaeis guineensis) fruit. It is used as an antiatherogenic, antihypertensive, anticancer, antidiabetic and to prevent vitamin A deficiency. In traditional medicine practices, RPO is given to an individual who is suspected to have ingested a poisonous substance. Industrial exposure of carbon tetrachloride (CCl4), an environmental/industrial toxicant, is found more among individuals who work in resin and refrigerant manufacturing companies. Purpose: This study was carried out to evaluate the protective effect of RPO against CCl4 toxicity in rats. The study was also conducted to give insight on the concentrations of RPO that can abate this toxicant. Methods: The experimental Wistar rats were randomly grouped and treated as follows: Group 1 served as normal control, group 2- negative control, groups 3, 4 and 5 received daily 2, 4, 6 mL/kg RPO respectively for 14 days. Thirty (30) min after the 14th day treatment with RPO, the rats in groups 2-5 received intraperitoneally a single dose of 1 mL/kg CCl4 diluted in olive oil. After 24 h of CCl4 administration, the rats were humanely sacrificed; blood, liver and kidney were collected. Hepatorenal, lipid, antioxidant and haematological indices were evaluated and liver and kidney histopathology were examined. Results: The rats treated with RPO had significant (P < 0.05) increase in the packed cell volume, haemoglobin and platelet, and dose dependently decreased in the alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase activities when compared to the negative control. Except the urea value of the negative control, no significant effects (p>0.05) were observed in the kidney function parameters. There were observable significant increases (P < 0.05) in glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) levels in RPO-treated groups when compared to the negative control. Conclusions: Pretreatment with RPOhas a protective effect against CCl4 toxicity by increasing GSH, SOD, CAT and decreased malondialdehyde levels, and increased red blood cell indices. This shows that RPO has a potential to abate the toxic effect of carbon tetrachloride on hepatorenal as well as haematopoietic organs in Wistar rats.